HUBUNGAN SIPIL-MILITER DI CHILE PASCA AUGUSTO PINOCHET, 1990-2006 - Zainal, Nur Aliyah (JPP (Jurnal Politik Profetik), 2013)
This paper is about the efforts of civilian government of Chile to subordinate its military since 1990 until 2006. Every government has its own strategy to do so. The strategies of every civilian government seek for supremacy, but the corporate interest of military often restricts it. The Chilean government’s policies that intervene the military institution and damage the corporate interest could be a negative impact on the armed forces. Policies of civilian governments to military especially Pinochet’s issue and human right abuses have a strong impact on instability of the country. Finally, the defense policy of “division of sphere” of Ricardo Lagos not to intervene the military and also the commitment of military especially army to be more professional post Pinochet, have been successful in establishing civil supremacy in Chile.